Antiviral Herbs in Ayurveda - Singh, Srishti; Prasad, Rajendra (International Research Journal of Ayurveda & Yoga, 2021)
Viral infections constitute a major public health concern and accounts for global socioeconomic burden, much more in developing nations. Emergence of new viral epidemics, their rapid, devastating worldwide spread and failure to develop new antiviral drugs at such pace have made it a priority to discover new antiviral agents. There is a greater need to develop antiviral drugs with better efficacy, safety, oral bioavailability, utility at both prophylaxis and treatment stages and at last which prevents drug resistance. Medicinal plants have great potential to fulfil above requirements. Several plants provide a rich source for drug discovery against both infectious and non-infectious diseases. Many plant metabolites possess broad-spectrum antiviral action. Plant kingdom is very diverse and is an unlimited source of new drugs. Plant extracts can prove to be more effective, safe and economical to areas which have limited resources. This article is an attempt to highlight the potent antiviral action of some medicinal plants; which may be beneficial in providing important lead in developing new antiviral drugs.